IDEATIONAL GRAMMATICAL METAPHORS IN EDITORIALS TEXTS OF THE JAKARTA POST NEWSPAPER - Kiky Wardhani; Siti Aisyah Ginting; Sumarsih Sumarsih (Universitas Negeri Medan, 2019)
This study was investigated the realization of ideational grammatical metaphors in editorials of The Jakarta Post Newspaper. The objectives of this study were to identify the types of ideational grammatical metaphor are found in editorials texts of, to describe how the ideational grammatical metaphor lingustically realized in the editorials text, and to explain the reasons for the used of ideational grammatical metaphors. This study was conducted by using descriptive qualitative research. The sourceof data were editorials of The Jakarta Post newspaper, published on http://www.thejakartapost.com/chanel/editorial, which containing of six editorials written in January 2015 episode. The data were the texts containing of ideational grammatical metaphors. The data were analyzed based on the Sistemic Functional Language approach. The result showed that there were four types of ideational grammatical metaphor, namely adjective =>noun, verb =>noun, verb =>adjective, adverb =>adjective. The dominant type of ideational grammatical metaphor in the editorials is verb =>adjective. The reasons of ideational grammatical metaphor used in the editorials was due to nominalization and condensation. Grammatical metaphor as a model of language was needed to help people to understand how a text work to make meaning and all meaning was situated in context of situation and context of culture. There was a great deal of variation among different register in the degree and types of metaphor that was encountered. Register of field is social action of which is going on the text of editorials texts.Key words: Ideational Grammatical Metaphor, Texts, The Jakarta Post newspaper,